Analisis Paparan Co Dan So2 Pada Petugas Parkir di Basement Mall Ska di Kota Pekanbaru - Damri, Damri; Ilza, Mirna; Afandi, Dedi (Dinamika Lingkungan Indonesia, 2016)
Abstrak: The objectives in research on the effects of CO and SO2 to ilness parking attendant is to analyze ilness suffered a parking attendant at the Mall SKA Pekanbaru in working on indoor parking. The description of the illness suffered a parking attendant at SKA Pekanbaru Mall is 21.3% feel the illness, sometimes reaching 33.2% and 45.4% never reached. Exposure to CO over high concentration at night and exposure to SO2 evenly in the morning, afternoon and evening. There is a real impact concentration of CO exposure to the pain felt by the parking attendant. This pain can be perceived from the parking attendants to the environmental conditions the parking lot itself. The condition is more common at night. Then the results related to the impact of SO2 exposure to pain proved to be a significant impact on the illnes parking attendant.